2019
DOI: 10.1590/0103-6440201902416
|View full text |Cite|
|
Sign up to set email alerts
|

Infrared Light-Emitting Diode (LED) Effects on Orthodontic Tooth Movement

Abstract: The present study aimed to analyze the effect of LED phototherapy on the presence of hyalinization and root resorption during orthodontic tooth movement (OTM) in rats and to measure the amount of tooth movement. Eighty rats were allocated into two groups: LED and control (CON), where the LED rats were irradiated with infrared LED (850 nm, 30 mW) for 5 min during the first five days of OTM and where controls were not irradiated. Both groups were subdivided into four subgroups (n=10) according to the date of eut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…3D evaluation premises reliable image segmentation which can be particularly challenging when metal artifacts are present, or when histograms overlap. [16][17][18][19][20] Since mineral contents of cementum and bone were reported to be likewise [21], reliable approaches to segment tooth roots in μCT are an inevitable premise for volumetric assessment of OTM and RR in μCT.…”
Section: Introductionmentioning
confidence: 99%
“…3D evaluation premises reliable image segmentation which can be particularly challenging when metal artifacts are present, or when histograms overlap. [16][17][18][19][20] Since mineral contents of cementum and bone were reported to be likewise [21], reliable approaches to segment tooth roots in μCT are an inevitable premise for volumetric assessment of OTM and RR in μCT.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily established on histological investigations, pressure, and a tension side have also been recognized during the OTM procedure [7,8,10]. Hyalinization can be accordingly sterile necrosis at the pressure region of PDL observed amid the early phases of the OTM, and broad hyaline zones can thus result in imperative delay within the tooth movement procedure [7,11,12]. In related studies, hyalinization has been seemingly found within the initial phase of OTM, and small hyalinized patches have been additionally observed within the afterward phases [13,14].…”
Section: Introductionmentioning
confidence: 97%